The State of Internationalization in Canadian Higher Education - McBride, Karen (International Higher Education, 2016)
How do we increase the scale and scope of international experiences for students thereby ensuring that they have the knowledge, skills and competencies they need in a globalized world? This article examines the state of internationalization in Canadian higher education, the global engagement challenge for Canada and the need for a proactive, inclusive approach from institutions, governments and businesses.